Melanomacrophage centers and mucus cells of shorthorn sculpin (Myoxocephalus scorpius) as biomarkers of contaminants - Dang, TSM (2020)
Marine pollution has been a global issue as most marine ecosystems are affected by anthropogenic pollutants. Some common pollutants such as persistent organic pollutants (POPs) and heavy metals have become a widespread concern to environment and public health due to their toxicity, persistence and bioaccumulation. Environmental monitoring programs need to detect potential harmful effects of these pollutants before they affect high levels of biological organization such as population or ecosystem. This can be done using biomarkers in appropriate indicator species. Shorthorn sculpin (Myoxocephalus scorpius) has been used in this project as an indicator species for environmental studies in Greenland because the fish is abundant, easy to sample, benthic, sedentary and long-lived. Although sculpins have been used extensively in environmental monitoring programs in Greenland, most studies focused on increased concentrations of trace elements in various organs and some histopathology in fishes caught from polluted areas. Most significant histological alterations, in particular, melanomacrophage centers (MMCs) or mucus cells (MCs) were evaluated using qualitative or semi-quantitative methods. The overall aims of this thesis were to study MMCs and MCs in shorthorn sculpins and evaluate their biomarker potential for pollutant exposure. These were achieved by pursuing the following specific aims: a) Investigate MMCs in various organs of shorthorn sculpins and assess the biomarker potential of the splenic and renal MMC populations, and b) Investigate the MCs in the gills and skin of shorthorn sculpins using different quantification methods and examined their biomarker potential for pollutant exposure. This study characterised MMCs in all main organs including the gills, liver, spleen, kidney and pancreas of shorthorn sculpins. The variations in morphology, density, size, area, distribution, pigments and response to pathogens of the MMC populations in these organs were described and can be used as baselines for future ...